2020
DOI: 10.1021/acs.langmuir.0c01062
|View full text |Cite
|
Sign up to set email alerts
|

Polycation–Anionic Lipid Membrane Interactions

Abstract: Natural or synthetic polycations are used as biocides or as drug/gene carriers. Understanding the interactions between these macromolecules and cell membranes at the molecular level is therefore of great importance for the design of effective polymer biocides or biocompatible polycation-based delivery systems. Until now, details of the processes at the interface between polycations and biological systems have not been fully recognized. In this study, we consider the effect of strong polycations with quaternary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…6A). 37 The zeta potential measurements and calcein release experiments confirmed that PAM effectively adhered to the POPC/DOPA liposomes neutralizing anionic lipids but did not alter membrane permeability. In turn, hydrophobically modified polycations can penetrate the lipid bilayer by incorporating their alkyl groups and cause disorder in the acyl chains of the lipid molecules.…”
Section: Resultsmentioning
confidence: 75%
“…6A). 37 The zeta potential measurements and calcein release experiments confirmed that PAM effectively adhered to the POPC/DOPA liposomes neutralizing anionic lipids but did not alter membrane permeability. In turn, hydrophobically modified polycations can penetrate the lipid bilayer by incorporating their alkyl groups and cause disorder in the acyl chains of the lipid molecules.…”
Section: Resultsmentioning
confidence: 75%
“…The main reason for the toxicity of the carrier is that the cation can interfere with the structure of the cell membrane, which causes the death of the cell [ 28 ]. The positive charge of cationic compounds is a double-edged sword.…”
Section: Resultsmentioning
confidence: 99%
“…Polycation–polyanion complexes can cause adverse effects such as inflammation [ 34 , 35 ]. On the other hand, cationic compounds can impair the liver function [ 36 , 37 , 38 ], interact with anionic cell lipid membranes [ 39 , 40 ], impact clot morphology [ 41 , 42 ], lyse erythrocytes [ 43 ], generate cellular [ 44 ] and hematological [ 45 , 46 ] toxicity, and increase LDH levels associated with inflammatory disorders [ 47 ]. Therefore, it is not clear if hepatotoxicity is associated directly with the HBC–ENX complexes or the excess of polycationic HBC.…”
Section: Discussionmentioning
confidence: 99%